2020
DOI: 10.1097/md.0000000000022891
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the miR-200 family in bladder cancer

Abstract: Background: We aimed to evaluate the prognostic significance of high expression of the miR-200 family of microRNAs in bladder cancer. Methods: Studies on the correlation between the miR-200 family and prognosis in patients with bladder cancer were searched in databases. Combined hazard ratios (HRs) were calculated based on HRs and 95% confidence intervals (CIs) for overall survival (OS), cancer-specific survival (CSS), and recurrence-free survival (RFS)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The overexpression of mir-200c and mir-141 is strongly associated with a better prognosis in bladder cancer patients. Our findings are consistent with Mei et al 2020 , with additional evidence for CNV-induced overexpression of hsa-mir-200c/mir-141. ROC/AUROC analysis indicated high diagnostic accuracy for hsa-mir-200c/mir-141 and hsa-mir-15b/mir-16-2 cluster members.…”
Section: Discussionsupporting
confidence: 93%
“…The overexpression of mir-200c and mir-141 is strongly associated with a better prognosis in bladder cancer patients. Our findings are consistent with Mei et al 2020 , with additional evidence for CNV-induced overexpression of hsa-mir-200c/mir-141. ROC/AUROC analysis indicated high diagnostic accuracy for hsa-mir-200c/mir-141 and hsa-mir-15b/mir-16-2 cluster members.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have reported the decreased expression of the miR-200 family in cancer tissues [ 18 , 19 ], and anti-cancer drug-resistant cancer cells [ 93 ]. The expression levels of miR-200 family miRNAs were shown to predict responses to anti-cancer therapeutics [ 19 , 20 , 21 , 22 , 23 , 24 ]. Thus, miR-200 family miRNAs can be a target for anti-cancer drug development.…”
Section: Discussionmentioning
confidence: 99%
“…The low expression of miR-200b was strongly associated with the poor survival of patients with hepatocellular carcinomas [ 22 ]. High levels of the miR-200 family were strongly associated with better survival of bladder cancer patients [ 23 ]. The high expression of miR-200b was correlated with better responses of lung cancer patients to immunotherapy involving anti-PD-l antibodies such as pembrolizumab [ 24 ].…”
Section: Mir-200 Family As a Diagnostic And Prognostic Markermentioning
confidence: 99%
“…Higher miR-200c expression was correlated with shorter overall survival in gastric cancer and non-small cell lung carcinoma ( 205 , 209 ). However, in another meta-analysis, the expression of miR-200 family members was associated with a better prognosis in bladder cancer as it correlated with longer overall survival, recurrence-free survival, and cancer-specific survival ( 210 ). Moreover, miR-200c correlated with a better prognosis in ovarian cancer ( 211 ).…”
Section: Expression Of Mir-200 Family In Cancermentioning
confidence: 99%